Conformational impact of aliphatic side chains in local anaesthetics: benzocaine, butamben and isobutamben. Issue 45 (30th April 2020) - Insausti, A.; Calabrese, C.; Parra, M.; Usabiaga, I.; Vallejo-López, M.; Écija, P.; Basterretxea, F. J.; Grabow, J.-U.; Caminati, W.; Lesarri, A.; Cocinero, E. J.
Abstract : A comprehensive conformational analysis and the impact of side chains on local anaesthetics in the case of benzocaine, butamben and isobutamben. Abstract : We studied the impact of aliphatic side chains on the stability and conformational landscape of the local anaesthetics benzocaine, butamben and isobutamben, combining high-resolution rotational spectroscopy in the microwave and millimetre regions and molecular modelling. The study reveals the connections between alkyl chain flexibility and molecular conformations.